The Enigma of Sponge-Derived Terpenoid Isothiocyanate–Thiocyanate Pairs: A Biosynthetic Proposal - Tadeusz F. Molinski (Marine Drugs)
The co-occurrence of rare terpenoid thiocyanates (R-SCN), structurally similar to their more common isothiocyanate isomers (R-NCS), poses an enigma: how does the accepted path, terpenyl cation R+ → R-NC → R-NCS, accommodate R-SCN? The mystery can now be rationalized by the consideration of three biosynthetic motifs: terpenoid carbocation (R+) capture by cyanoformate, NC-COOH (itself in equilibrium with NC− and CO2); co-localized rhodanese (a dual-function enzyme) that can both convert fugitive inorganic NC− to thiocyanate ion, NCS−, and alkyl isonitriles to alkyl isothiocyanate (R-NC → R-NCS) and adventitious capture of the NCS− by R+. The former two scenarios explain the preponderance of isothiocyanates, R-NCS, as products of a linear reaction path—the α-addition of S0 to R-NC—and the third scenario explains minor, less stable thiocyanates, R-SCN, as products of the adventitious capture of liberated NCS− by the penultimate R+ precursor. DFT calculations support this proposal and eliminate other possibilities, e.g., the isomerization of R-NCS to R-SCN.